Learning competencies in the electrical installations laboratory for engineering students - Murillo Manrique, Margarita F.; Sánchez Ayte, Jorge A.; Meléndez Murillo, Antonio A. (Institute of Advanced Engineering and Science, 2025)
The research addresses the lack of practical competencies in the electrical installations-I (IE-1) course at the School of Mechanical and Electrical Engineering (EPIME) at the National Technological University of Lima Sur, where the current content is mostly theoretical. To solve this problem, the course was moved to the Electrical Installations Laboratory (LABIE) and the conceive, design, implement, and operate (CDIO) methodology was applied, combining theory with practice to develop competencies in knowledge, skills, and attitudes. The laboratory guides were aligned with the new IE-1 syllabus, including single-phase and three-phase systems of 220 V at 60 Hz, which were not previously covered. Two groups of 15 students were compared: an experimental group (EG) and a control group (CG). Both took a pre-test with similar results. The CG followed traditional classes, while the EG worked in the LABIE with CDIO. At the end, a post-test showed significant improvements in the EG, validating the effectiveness of CDIO in enhancing practical training in IE-1. It is concluded that this methodology should be implemented in the new EPIME curriculum.